Experimental observations of nonlinear vibration localization in a cyclic chain of weakly coupled nonlinear oscillators. (14th April 2021) - Niedergesäß, B.; Papangelo, A.; Grolet, A.; Vizzaccaro, A.; Fontanela, F.; Salles, L.; Sievers, A.J.; Hoffmann, N.
Abstract: Experimental results on nonlinear vibration localization in a cyclic chain of weakly coupled oscillators with clearance nonlinearity are reported. Numerical modelling and analysis complements the experimental study. A reduced order model is derived and numerical analysis based on the harmonic balance method demonstrates the existence of multiple classes of stable spatially localized nonlinear vibration states. The experiments agree very well with the numerical results. The findings suggest that vibration localization due to fundamentally nonlinear effects may also arise in mechanical structures with relevance in engineering.